Kampanye Edukasi Kesehatan Masyarakat Masjid: Membangun Kesadaran tentang Bahaya Overhidrasi - Arini, Aida; Mughiroh, Ainun Fitri; Anshori, Sholihul; Niswah MZ, Isniyatun; Surur, Shobihus; Said, Ali; Nuruddin, Muhammad (Unity Academy, 2025)
Public awareness of maintaining body fluid balance has largely focused on preventing dehydration, while the dangers of overhydration are often overlooked. This condition can lead to hyponatremia, which poses serious neurological risks and may result in death. The issue oflow health literacy regarding overhydration prompted the implementation of a mosque-based community service program as a center for health education. This activity aimed to enhance the knowledge and awareness of mosque communities about the dangers of excessive water consumption and to encourage more mindful drinking behavior. The solution was implemented through a participatory approach, consisting of interactive health counseling, group discussions, distribution of educational media (leaflets, posters, videos), and digital campaigns led by mosque youth. Program effectiveness was evaluated using pre-test and post-test and qualitative observations of community responses. The results showed a 75% increase in average knowledge scores and a significant behavioral change, with 70% of participants adjusting their water consumption according to body needs. Additionally, a community group called “Healthy Mosque Friends” was established as a sustainability effort. This program contributed to strengthening the mosque’s role as a center for community-based health promotion that is communicative, religiously grounded, and sustainable. Thus, this health education campaign not only improved public health literacy about overhydration but also fostered a collective awareness of maintaining fluid balance as part of both spiritual and social responsibility.